Why is welfare provision unpopular in China?. Issue 8 (16th November 2020) - Chang, Alex C. H.
ABSTRACT: This article analyses from a cultural perspective why, despite exacerbating income inequality, Chinese people are not in favour of income equality. I argue that the patriotic education campaign initiated in the 1990s encouraged citizens to sacrifice for the greater good of China and caused the Chinese to accept and adapt to a decrease in governmental welfare as well as lessening the demand for it, thus reducing the government's financial burden of welfare provision. I then test the hypothesis against the Asian Barometer Survey data. The statistical results support my assertion, suggesting that strong patriotic beliefs reduce the preference for social equality, and that private income and economic perspectives do not significantly stimulate the public demand for redistributive policies in China.